2016
DOI: 10.1177/1350650116654803
|View full text |Cite
|
Sign up to set email alerts
|

Orifice compensated performance characteristics of hybrid hole-entry conical journal bearing

Abstract: Influence of semi-cone angles on the performance of the non-recessed hybrid/hydrostatic hole-entry conical journal bearing compensated with orifice restrictor has been carried out analytically. The analysis comprises two rows of symmetric hole-entry contour in the circumferential direction of hybrid/hydrostatic conical journal bearing. An orifice restrictor is used in the hole-entry contour to allow the restricted flow in the clearance space of a journal and bearing. Well-known finite element method and Newton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Reynolds equation is applied to lubricant flow field for the given boundary conditions (Khakse et al, 2017):…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reynolds equation is applied to lubricant flow field for the given boundary conditions (Khakse et al, 2017):…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Reynolds formula in the spherical coordinate form for conical hole-entry journal bearing in hybrid mode is as follow (Khakse et al , 2017): …”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…These classes of bearings when designed appropriately perform superior to multi recessed bearing with the appropriate characteristics of hydrodynamic bearings at high speed and hydrostatic bearings at low speed. A thorough literature review [15][16][17]…”
Section: Introductionmentioning
confidence: 99%
“…Also, Khaske et al. 32 described the performance of orifice-compensated HEHCJB and suggested hybrid bearing for the improved performance. Recent paper of Kumar and Varma 33 reveals that the noncircular bearing using CFV restrictor with micropolar lubricant is better than the circular bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Rajput and Sharma 30,31 reported an enhanced performance with micropolar lubricated bearing vis-a`-vis Newtonian lubricated bearing and the influence of geometric irregularities on the performance of misaligned hybrid journal bearing with membrane restrictor, respectively. Also, Khaske et al 32 described the performance of orifice-compensated HEHCJB and suggested hybrid bearing for the improved performance. Recent paper of Kumar and Varma 33 reveals that the noncircular bearing using CFV restrictor with micropolar lubricant is better than the circular bearing.…”
Section: Introductionmentioning
confidence: 99%